Cultivation of lacrimal gland acinar cells in a microgravity environment. Issue 8 (4th May 2009) - Schrader, S; Kremling, C; Klinger, M; Laqua, H; Geerling, G
Abstract : Background: A rotary cell-culture system (RCCS) allows the creation of a microgravity environment of low shear force, high-mass transfer and three-dimensional cell culture of various cell types. The aim of the study was to evaluate the growth pattern and the secretory function of rabbit lacrimal gland acinar cells in a microgravity environment using an RCCS. Methods: Lacrimal gland acinar cells from male New Zealand White rabbits were isolated and cultured in an RCCS up to 28 days. Cells were analysed by light and electron microscopy, and apoptosis was assessed by the TUNEL assay at days 7, 14, 21 and 28. Secretory function was tested by measuring the β-hexosaminidase activity. Results: After 7 days of culture, spheroidal aggregates were found inside the RCCS. The spheroids consisted of acinus-like cell conglomerates. Apoptotic centres inside the spheroids were observed at all time points by means of the TUNEL assay. Evaluation of the secretory function revealed β-hexosaminidase release after carbachol stimulation which decreased over the culture period. Conclusion: A simulated microgravity environment promotes the development of three-dimensional cell spheroids containing viable acinar cells up to 28 days. Due to the evolving central apoptosis, it is unlikely that such simple three-dimensional cell communities can serve as tissue equivalents for clinical transplantation, but they promise opportunities for further applications in basic and applied cell research on lacrimal gland cells.